PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI KEGIATAN KEAGAMAAN MUJAHADAH di PONDOK PESANTREN KEDUNGLO II KEPANJEN MALANG - Deviena Anisatus Sholiha; Fathurrahman Alfa; Qurroti A'yun (VICRATINA, 2021)
Forming human character into a religious character can be started with daily habits. Because basically religious activities do not only occur when worshiping but also by carrying out other activities that are driven by supernatural powers. In pesantren life, apart from inculcating cognitive effective and psychomotor domains in the learning process, pesantren also has three main domains: Faqohah (adequacy or deep understanding of religioun, Thabiah (temper character, or character) and Kafa’ah (operational skills). This research is descriptive qualitative research type of field research using interview, ovservation and documentation. In addition, reasearchers analysed using data collection, data review dan data conclusion